The Educational and Religious Values on Bimanese Tradition Custom of Rimpu Tembe; A Study at Sambori Village - Ilham Ilham (Linguistics and ELT Journal, 2017)
Rimpu is the typical dress of womenofBimanese formed from a traditional sarong woven. The use of Rimpu done by one of the holes or the end of the sheath wrapped around the head so that only the visible face for women who are married (RimpuColo) and just looking eyes for the girl (RimpuMpida). Rimpu is local wisdom and becomes part of the wealthofBimanese Islamic culture that needs to be preserved. The purpose of the study is to investigate the effect of RimpuTembetraditional custom of Bimanese toward the educational and religious values at Sambori village. The method of this study is a qualitative method and the data was collected by using observation, interviews, documentation, and recording. The result the shows that Educational values that can be obtained from Rimpu are when women wear Rimpu for their activity must be when they traveling or meeting with male and others. Rimpu can protect women from the lust of the opposite sex. Religious values of RimpuTembe is the moral values, faith and sari'ah, because of their body Islamic beliefs.